PEMBINAAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MEMBIASAKAN PESERTA DIDIK SHALAT BERJAMAAH DI SMPN 2 BUKITTINGGI - Nora Fadila; Deswalantri Marahzali; Suryanti Suryanti (KOLONI, 2022)
Education teacher development is a method or step used by Islamic religious education teachers in providing guidance and training in education, especially in prayer education so that students can become disciplined in carrying it out. It is seen that many students lack discipline in praying, especially the noon prayers in congregation at school because there are still those who are doing their assignments, there are also those who gather with their friends and they don't immediately take ablution for prayer. The research in this article aims to allow researchers to find out how the guidance used by Islamic religious education teachers in instilling discipline in students' prayer worship at SMPN 2 Bukittinggi so that students obey God's commands and do not neglect their prayers. The type of research that the authors use in this article is descriptive qualitative research, namely describing events in the field. In this research article the author tries to describe and explain the guidance of Islamic religious education teachers in instilling the discipline of praying in students at SMPN 2 Bukittinggi. The data collection techniques that the authors use are observation, interviews, and documentation. The data analysis techniques used are data reduction, data display, and data verification. The results of research on coaching Islamic religious education teachers in getting used to praying in congregation, there are several coachings that are used, namely as follows: 1) supervision. 2) understanding. 3) motivation. 4) reinforcement. Keywords: PAI Teacher Development, Familiarize Congregational Prayers, Students